Relative Contribution of the ABC Transporters Cdr1, Pdh1, and Snq2 to Azole Resistance in Candida glabrata - Whaley, Sarah G. (Antimicrob Agents Chemother, 2018)
The utility of the azole antifungals for the treatment of invasive candidiasis is severely hampered by azole resistance in Candida glabrata. This resistance is mediated almost exclusively by activating mutations in the zinc cluster transcription factor Pdr1, which controls the genes encoding the multidrug resistance transporters Cdr1, Pdh1, and Snq2. However, the specific relative contributions of these transporters to resistance are not known. To address this question, the SAT1 flipper method was used to delete CDR1, PDH1, and SNQ2 in a strain of C. glabrata engineered to carry a clinically relevant activating mutation in PDR1. Susceptibility testing was performed according to the CLSI guidelines, with minor modifications, and confirmed with Etest strips. Of the single-transporter-deletion strains, only the CDR1 deletion resulted in a decreased azole MIC. The deletion of PDH1 in combination with CDR1 resulted in a moderate decrease in MIC compared to that observed with the deletion of CDR1 alone. SNQ2 deletion only decreased the MIC in the triple-deletion strain in the absence of both CDR1 and PDH1. The deletion of all three transporters in combination decreased the MIC to the level observed in the PDR1 deletion strains for some, but not all, azoles tested, which indicates that additional Pdr1 targets likely play a minor role in this process. These results indicate that while Cdr1 is the most important Pdr1-mediated multidrug resistance transporter for azole resistance in this clinical isolate, all three of these transporters contribute to its high-level resistance to the azole antifungals.